Respon Ayam Broiler Terhadap Penggunaan Onggok Dalam Ransum Sebagai Pengganti Sebagai Jagung - Amir Hasan Lubis (Agricultural Faculty, 2002)
ABSTRACT.Studies on response of broiler to utilization of cassava meal as substitute for cron diet were conducted using seventy two unsexed hubbard strain broiler chiks. A completely randomized design, with four treatment and six replicates was used and this study. Four treatment consisting of cassava meal were supplemented in each ration at graded level of 0%, 10 %, 20%, and 30%. Each treatment contains 22.5% protein and 3000 cal/kg ration metabolized energy. The result showed there were no significant effects of the four level of cassava meal on body weight, feed consumption, feed conservasion, percentage of abdominal fat. The average body weight for each treatment was 1508.91,1454.99,1417.31 and 1401.95 gram, respectively. Feed conservation was 1.72, 1.72, 1.72 and 1.74 gram, respectively. Percentage of abdominal fat was 2.64, 2.87, 3.11 and 3.14%, respectively. There was a tendency that the increasing level of cassava meal in ration will decresease body weight and feed consumtion. It could be concluded that utilization of cassava meal up to 30% to substitutebcorn in the ration might recommended.